2023
DOI: 10.18388/abp.2020_6621
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the pharmacological and biochemical effects of Salvia hispanica (Chia seed) against oxidized Helianthus annuus (sunflower) oil in selected animals

Abstract: Oil oxidation is important in terms of taste, nutritive component quality and toxic effect of the oil. In this study, the oxidized sunflower oil was used along with chia seed in rabbits for the determination of its effects on various hematological and serum biochemical parameters as well as on liver histopathology. Three rabbits were fed with oxidized oil (obtained by heating) at the dose rate of 2 ml/kg body weight by mixing it with green fodder. The other rabbit groups were fed with Chia seed at dose rate of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Therefore, the binding energy of standard drug was also higher than the C. paradisi leaf components such as geraniol and betapinene. The protein TRPV4 is selected as analgesic protein and it is confirmed by previous literature (22,(47)(48)(49)(50)(51)(52)(53). The docking of TRPV4 was done with 2 ligand molecules (geraniol and beta-pinene) and diclofenac is used as standard drug.…”
Section: Selected Amino Acids For 3 Proteinsmentioning
confidence: 73%
“…Therefore, the binding energy of standard drug was also higher than the C. paradisi leaf components such as geraniol and betapinene. The protein TRPV4 is selected as analgesic protein and it is confirmed by previous literature (22,(47)(48)(49)(50)(51)(52)(53). The docking of TRPV4 was done with 2 ligand molecules (geraniol and beta-pinene) and diclofenac is used as standard drug.…”
Section: Selected Amino Acids For 3 Proteinsmentioning
confidence: 73%
“…Salvia hispanica L., also known as chia, is a herbaceous plant belonging to the Plantae kingdom, Lamiaceae family, Salvia genus, and Hispanic species [ 25 ]. This seed is grown commercially in Mexico, Guatemala, Bolivia, Australia, Peru, Argentina, America, and Europe [ 26 , 27 ]. Of the 900 seed species of the Lamiaceae family, 61 are commercially cultivated in Brazil [ 28 ].…”
Section: Chia Seedmentioning
confidence: 99%
“…Moreover, 25% of the ingredients used in pharmaceuticals are derived from medicinal plants (Robbers et al, 1996). Several studies have demonstrated that herbal medicines Evaluation of therapeutic potential of Dianthus crinitus using mice as a research animal from the Vedic era have been used for treating various disorders, such as heart diseases, cancer, digestive system diseases, central nervous system (CNS) diseases, diabetes, and inflammatory diseases (Ahmad et al, 2023a;Aqib et al, 2023;Ayesha et al, 2022;Aziz et al, 2023;Ejaz et al, 2023;Hussain et al, 2023;Naveed et al, 2022;Nureen et al, 2023;Rauf et al, 2023;Zawar et al, 2023).…”
Section: Introductionmentioning
confidence: 99%